Code Switching in Instagram - Dimas Fisal Bilillah; Faishal Arkan (Journalistics: Journal of English Teaching and Applied Linguistics, 2022)
Code switching is currently very common, both in direct and indirect communication and on social media. This study aims to describe the forms and factors of the use of code switching used on Instagram. Researchers know that there are three types of code switching found on Instagram accounts used by Instagram users, namely: tag switching, intersentential code switching, and intrasetential code switching. Then after analyzing by type, the researcher found the reasons for using code switching there were four points: topic change, lack of vocabulary, bilingual/multilingual, Prestige and trend. Then the researchers used qualitative research methods in conducting the analysis. This research is expected to be useful in the language learning process, especially sociolinguistic studies and language use.